Trans-kingdom fungal pathogens infecting both plants and humans, and the problem of azole fungicide resistance - Pintye, Alexandra; Bacsó, Renáta; Kovács, Gábor M. (Frontiers in Microbiology, 2024)
Azole antifungals are abundantly used in the environment and play an important role in managing fungal diseases in clinics. Due to the widespread use, azole resistance is an emerging global problem for all applications in several fungal species, including transkingdom pathogens, capable of infecting plants and humans. Azoles used in agriculture and clinics share the mode of action and molecular structures facilitating cross-resistance development. The extensive use of azoles in the environment, e.g., for plant protection and wood preservation, contributes to the spread of resistant populations and challenges using these antifungals in medical treatments. The target of azoles is the cytochrome p450 lanosterol 14-α demethylase encoded by the CYP51 (commonly called also as ERG11 in the case of yeasts) gene. Resistance mechanisms involve mainly the mutations in the coding region in the CYP51 gene, resulting in the inadequate binding of azoles to the encoded cyp51 protein, or mutations in the promoter region causing overexpression of the protein.The World Health Organization (WHO) has issued the first fungal priority pathogens list (FPPL) to raise awareness of the risk of fungal infections and the increasingly rapid spread of antifungal resistance. Here, we review the main issues about the azole antifungal resistance of trans-kingdom pathogenic fungi with the ability to cause serious human infections and included in the WHO FPPL. Methods for the identification of these species and detection of resistance are summarized, highlighting the importance of these issues to apply the proper treatment.